A porous supramolecular ionic solid. Issue 59 (30th June 2021) - Jackson, Nathan; Vazquez, Irma Rocio; Chen, Ying-Pin; Chen, Yu-Sheng; Gao, Wen-Yang
Abstract : Charge decoration provides a new synthetic strategy to integrate discrete coordination cages into an extended permanently porous material. Abstract : We report a synthetic strategy to integrate discrete coordination cages into extended porous materials by decorating opposite charges on the singular cage, which offers multidirectional electrostatic forces among cages and leads to a porous supramolecular ionic solid. The resulting material is non-centrosymmetric and affords a piezoelectric coefficient of 8.19 pC N −1, higher than that of the wurtzite ZnO.